UJI AKTIVITAS SALEP EKSTRAK SERAI (Cymbopogon nardus) TERHADAP PENYEMBUHAN LUKA BAKAR PADA TIKUS PUTIH JANTAN (Rattus norvegicus) - Ariani Syahputri, Shinta; Pima Sari Tambunan, Efrida; Syukriah (Jurnal Biogenerasi, 2024)
Burns are damage that occurs to skin tissue due to direct contact with the surface of the body. The healing process of burn wounds can be accelerated by using traditional plants, namely lemongrass. The aim of this research was to determine the effect of lemongrass extract ointment in healing second degree burns and to determine the most effective dose of lemongrass extract ointment in healing burns in rats. This study used a completely randomized design, rats were divided into five treatments, namely K- (given vaseline), K+ (brand X ointment), P1 (5% extract ointment), P2 (10% extract ointment), P3 (15% extract ointment). Mice were given burns on the right back with an area of ​​3 cm x 2 cm, the area of ​​the wound was measured for 15 days. The results of statistical tests using One-way ANOVA and further tests with Duncan showed that there was no significant effect between the K+ treatment group (given bioplaceton) and treatment 3 (15% extract ointment). Based on the research conducted, it can be concluded that the P3 group (15% lemongrass extract ointment) with a remaining wound area of ​​1.26 cm is the most optimal treatment in accelerating the healing of burn wounds in mice.